2011
DOI: 10.1016/j.pain.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fibromyalgia syndrome after whiplash injuries: Methodologic issues

Abstract: Problems in diagnosing FM among motor vehicle collision (MVC) patients with whiplash (WL) include: the predominance of tender points (TPs) in the neck/shoulder girdle region; the 3-month duration of widespread pain criterion; and, the stability of diagnosis. The present study examined the prevalence of FM in a cohort (N = 326) with persistent neck pain 3 months following WL injury who were enrolled in a treatment program. Physical examinations were performed at baseline and at the end of treatment. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Our findings were consistent with a previous study done by Robinson et al. [23]. They investigated the prevalence of FM in a cohort of individuals with persistent neck pain 3 months after a whiplash injury and reported that the participants with FM preferentially reported tenderness in neck/shoulder girdle muscles compared with distal muscles.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings were consistent with a previous study done by Robinson et al. [23]. They investigated the prevalence of FM in a cohort of individuals with persistent neck pain 3 months after a whiplash injury and reported that the participants with FM preferentially reported tenderness in neck/shoulder girdle muscles compared with distal muscles.…”
Section: Discussionsupporting
confidence: 93%
“…They investigated the prevalence of FM in a cohort of individuals with persistent neck pain 3 months after a whiplash injury and reported that the participants with FM preferentially reported tenderness in neck/shoulder girdle muscles compared with distal muscles. They emphasized that 10 TPs are located around the neck and shoulder regions and this may bias the diagnosis of FM in patients with motor vehicle collision [23]. This also has to be taken into account when considering a diagnosis of FM in patients with CDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of CS has been demonstrated in CSS populations by comparing the pain thresholds of CSS patients to the thresholds of pain-free controls to various stimuli (such as electrical, pressure, cold, and heat). Objective measures of CS, which complement subjective self-report, include brain imaging and nociceptive spinal reflex tests 24,25,43 , CS is associated with allodynia, hyperalgesia (excessive sensitivity to a normally-painful stimulus), expansion of the receptive field (pain extending beyond the area of peripheral nerve supply), and unusually prolonged pain after a painful stimulus has been removed (usually throbbing, burning, tingling, or numbness). 44 CS has been proposed as the root etiology for “Central Sensitivity Syndromes” (CSSs) 15,30,41 , which refer to a group of medically-indistinct disorders for which no organic cause can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Most research assumes that fi bromyalgia is stable and chronic. 11 , 12 , 13 Treatments resulting in loss of the fi bromyalgia diagnosis involved relaxation training or exercise in a rheumatology clinic, 11 cognitive behavioral therapy, 12 and an interdisciplinary treatment at a community pain clinic. [7][8][9][10] The small number of studies that have examined fi bromyalgia diagnosis changes have all examined fi bromyalgia as the primary diagnosis and found that 30% to 70% of patients lost the diagnosis after discharge.…”
mentioning
confidence: 99%